PENGARUH HYPNOBIRTHING TERHADAP NYERI PERSALINAN DI KECAMATAN SUNGAI TARAB KABUPATEN TANAH DATAR TAHUN 2015 - Hidayati, Hidayati (LPPM Universitas Prima Nusantara Bukittinggi, 2017)
Adolescent knowledge is very influential on the behavior in maintaining and cleaning the reproduction, because the higher the level of knowledge, it is expected to arise a positive attitude in maintaining personal hygiene. The Initial field study conducted found that 4 out of 5 female students (80%) do not understand about menstruation and how to deal with it. The purpose of the study to determine the effect of health promotion on menstruation to increase the attitude and hygiene of grade VII students at SMPN 2 Bukittinggi. The research design was a quasi-experimental study with one group pre-post test design. This research was conducted in March-April 2017 in grade VII students at SMPN 2 Bukittinggi with a total sample of 66 people. There is the influence of health promotion about menstruation in adolescent girls to increase knowledge attitude of the student of class VII at SMPN 2 Bukittinggi year 2017 with p-value = 0,0001 (Î± = 0,05). There is the influence of health promotion about menstruation in adolescent girls to increase knowledge of Hygiene grade VII student at SMPN 2 Bukittinggi 2017 with p-value = 0,0001. (Î± = 0.05). It is expected that health services, especially Puskesmas as early health services, are expected to increase the promotion of health, especially on adolescent reproductive health issues.